2015
DOI: 10.1002/jaba.262
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating a tablet application and differential reinforcement to increase eye contact in children with autism

Abstract: We tested the effectiveness of a tablet application and differential reinforcement to increase eye contact in 3 children with autism. The application required the child to look at a picture of a person's face and identify the number displayed in the person's eyes. Eye contact was assessed immediately after training, 1 hr after training, and in a playroom. The tablet application was not effective; however, differential reinforcement was effective for all participants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 11 publications
0
11
0
2
Order By: Relevance
“…Many studies have targeted the behavioral topography of eye contact in individuals with ASD and other developmental disorders, outside of the functional context of RTN. For example, interventions have been designed to increase eye contact following instructions like "look at me" (Foxx, 1977;Hall, Maynes, & Reiss, 2009), as a component of joint attention (e.g., Dube, 2004;Kryzak & Jones, 2015;Taylor & Hoch, 2008;Whalen & Schreibman, 2003), as a way to assess interest during conversations (Peters & Thompson, 2015;Stewart, Carr, & LeBlanc, 2007), and concurrent to making requests (Carbone, O'Brien, Sweeney-Kerwin, & Albert, 2013;Jeffries, Crosland, & Miltenberger, 2016;Ninci et al, 2013). However, to date only two studies have evaluated treatments for increasing eye contact in the functional context of RTN for children with ASD.…”
mentioning
confidence: 99%
“…Many studies have targeted the behavioral topography of eye contact in individuals with ASD and other developmental disorders, outside of the functional context of RTN. For example, interventions have been designed to increase eye contact following instructions like "look at me" (Foxx, 1977;Hall, Maynes, & Reiss, 2009), as a component of joint attention (e.g., Dube, 2004;Kryzak & Jones, 2015;Taylor & Hoch, 2008;Whalen & Schreibman, 2003), as a way to assess interest during conversations (Peters & Thompson, 2015;Stewart, Carr, & LeBlanc, 2007), and concurrent to making requests (Carbone, O'Brien, Sweeney-Kerwin, & Albert, 2013;Jeffries, Crosland, & Miltenberger, 2016;Ninci et al, 2013). However, to date only two studies have evaluated treatments for increasing eye contact in the functional context of RTN for children with ASD.…”
mentioning
confidence: 99%
“…In a recent demonstration of indirect training procedures, Jeffries, Crosland, and Miltenberger (2016) found that eye contact increased for three children with ASD aged 3 to 7 years when each child was required to make eye contact with a therapist prior to requesting preferred items. That is, therapists simply withheld requested items if the child did not make eye contact and provided the item only after the child provided eye contact before making a request.…”
mentioning
confidence: 99%
“…Berikut ini adalah penjabaran perubahan skor kuesioner saat sesi baseline, setelah sesi intervensi, dan saat sesi followup: (Foxx, 1977). Selain menggunakan prompt, seperti temuan penelitian sebelumnya (Carbone et al, 2013;Jeffries et al, 2016), kontak mata anak juga diperkuat dengan adanya pemberian extrinsic reinforcer, yaitu social reinforcer (misalnya, pujian) dan edible reinforcer (biskuit). Edible reinforcer juga berhasil digunakan sebagai extrastimulus prompt (menaruh makanan di depan pipi peneliti) untuk memicu kontak mata anak.…”
Section: Gambar 2 Presentase Penggunaan Prompt Dalam Memunculkan Perunclassified